Duration and frequency of catheterization in central vein stenosis: A case control study - Suhartono, Raden; Supit, Caroline (The New Ropanasuri Journal of Surgery, 2019)
Introduction. Placement of the central vein catheterization (CVC) is a major risk factor for central vein stenosis (CVS). Repetitive endothelial exposures to the CVC results in inflammation, microthrombi formation, hyperplasia of the intima, fibrosis and thus development of CVS. The study aimed to find out the correlation between the duration and frequency of CVC in patients with CVS. Method. A matched case-control study was conducted in dr. Cipto Mangunkusumo General Hospital. Samples were taken from the medical record. Multivariate statistical comparisons were done using Chi-square tests. Results. Fifty–four out of 717 patients underwent CVC for hemodialysis had CVS. A total of 32 patients with CVS enrolled in the study with 128 non–CVS patients as a control. Duration of CVC >6 weeks does not increase the risk of CVS (p = 0.207), whilst the odds ratio of CVS on the frequency of CVC >2 times is 30 times compared to those underwent 2 times increased the risk of CVS. Longer duration of CVC for hemodialysis did not increase CVS rate.